Piezo proteins, mechano reception and behaviour in Hydra - Alzugaray, Maria Eugenia (2025)
Cells are constantly exposed to mechanical forces. These stimuli must be detected and transduced to maintain homeostasis. Due that reason, mechano-sensory systems (MS) are present in all the organisms to generate appropriate responses. Piezo proteins are a recently discovered family of mechano-gated ion channels that responds to mechanical changes of the plasma membrane, allowing the influx of cations, mainly Ca2+. Piezo MS channels are widely represented in Metazoa, acting in several physiological systems. Hydra sp. is a freshwater member of the phylum Cnidaria which is assumed as the sister group of Bilateria. Despite the existence of Piezo channels in Hydra is known, their physiological roles remain unknown. In this work we delve into the physiological relevance of MS Piezo in responses associated to mechanical stimuli in Hydra sp. We analysed the effects of Jedi1 (a specific agonist of Piezo1) on the contractile behaviours, and cnidocyst discharge, and compared them with responses caused by natural stimuli. The results show that the activation of Piezo channels increases the contractile behaviour, stimulating the occurrence of contraction burst, a sudden kind of retraction observed in response to touch and osmotic stress. Cnidocyst discharge was also induced by Jedi1, resembling the response caused by the contact of the prey. The effects of both Jedi1 and natural stimuli were avoided in the presence of the inhibitor of MS channels GdCl3. The bioinformatic analysis shows that the protein predicted by Hydra genome has the characteristic motifs of Piezo proteins. These results are consistent with the existence of Piezo channels in Hydra, unveiling their physiological roles. Because of the relevance of Piezo channels in several pathological conditions and the high level of conservation in metazoans, Hydra could provide a significative experimental model to assay biological and pharmacological issues.